DIASPORA ETNIK JAWA DAN TRANSMISI BAHASA JAWA ANTARGENERASI DI SUMATRA UTARA - Wawan Prihartono (Ranah: Jurnal Kajian Bahasa, 2016)
Diaspora Javanese ethnic to North Sumatra driven at the time of the Dutch government in large quantities create their identity loss there now . Java language in North Sumatra did not survive as it should be. Javanese ethnic, prefers to use the Indonesian language in everyday communication rather than the Javanese language as a consequence of assimilation with the local culture, namely the Malay culture. This study aimed to describe the intergenerational transmission of the Java language in North Sumatra as a reference for the vitality of the Java language in there . The study used a qualitative descriptive method . As a result, intergenerational transmission of the Java language in North Sumatra show gradations drastic decline from generation to generation . The older generation does not transmit an javanese language to the next generation so well that indicated the Java language in North Sumatra are threatened with extinction.    ABSTRAKDiaspora etnik Jawa ke Sumatra Utara dalam jumlah yang cukup besar yang digerakkan pada zaman pemerintah Hindia Belanda membuat etnik Jawa di sana kehilangan identitas bahasanya. Bahasa Jawa di Sumatra Utara tidak bertahan sebagaimana mestinya. Etnik Jawa lebih memilih menggunakan bahasa Indonesia dalam komunikasi sehari-hari daripada bahasa Jawanya sebagai konsekuensi pembauran dengan kebudayaan lokal, yaitu budaya Melayu. Kajian ini bertujuan untuk mendeskripsikan transmisi bahasa Jawa antargenerasi di Sumatra Utara sebagai acuan vitalitas bahasa Jawa di sana. Kajian ini menggunakan metode deskriptif kualitatif. Hasilnya, transmisi bahasa Jawa antargenerasi di Sumatra Utara menunjukkan gradasi penurunan yang drastis dari generasi ke generasi. Generasi tua etnik Jawa tidak mentransmisikan bahasanya kepada generasi berikutnya dengan baik sehingga diindikasikan bahasa Jawa di Sumatra Utara sekarang dalam kondisi terancam punah.